La governance britannica della pluralità culturale di fronte all’applicazione di regole islamiche: tra tutele e antagonismi (Società e diritti, 2022)
In light of the failure of multicultural policies and call for interculturalism, the present contribution is dedicated tothe analysis of the legal means to protect Muslim minority in Britain, in an attempt to understand the current contextand the evolution of the relationship between the British common law system and the Islamic model. This essayreconstructs the policies aimed at the governance of diversity, by going through the multicultural model and theintercultural approach and by examining the official and unofficial application of Islam rules in England. Theanalysis of the English case shows the openness of the British common law system, but at the same time sheds lighton the controversy related to Islamic family law rules and practices, especially with respect to the resolution ofinterpersonal disputes by Islamic Alternative Dispute Resolution (ADR) institutions.